157 A Rare Case of Cutaneous-Urachovesicoenteric Fistula in a Patient with Crohn's Disease. (4th May 2021) - Ghanem, Y K M; Clarke, J; Jacob, T; Ahmad, N Z
Abstract: Background: Entero-Uracho Vesicle fistulae are a rare sequelae of aggressive Crohn's disease with only a small number of case reports being available in the literature. Such cases are most often managed via "SSNAP" principles with many Crohn's fistulas requiring complex surgical intervention to definitively deal with the offending fistulous tracts. We present a case with an even rarer consequence of uncontrolled Crohn's disease despite immunomodulatory therapy in a 34-year-old male who presented with a Entero-Uracho Vesicle fistula. We discuss the presenting symptoms and management protocol involved in this case. Case: A 34-year-old male with known Crohn's disease presented with an entero-uracho vesicle fistula, which further developed into a cutenaous-urachovesicoenteric fistula while awaiting surgery during his index admission. The fistula tract was confirmed via Computed Tomography with evidence of significant inflammation. Bowel rest, antibiotics, and nutritional support with Total Parenteral Nutrition preceded total excision of the fistulous tract with ileo-caecal resection of the diseased bowel with primary anastomosis, and resection of the urachus and closure of the cutaneous fistula site with desirable outcome. Patient completed a full-recovery with return of normal bowel function and nutritional status, with no delayed complications at 6-month follow-up.